INVENTARISASI JENIS-JENIS IKAN BUNTAL (FAMILI TETRAODONTIDAE) DI MUARA PERAIRAN BENGKALIS, KABUPATEN BENGKALIS, PROVINSI RIAU - Rudy Sangapta Ginting; Roza Elvyra; Yusfiati ' (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
This study was aimed to found puffer fish species belong to Tetraodontidae family from the estuary waters of Bengkalis Riau Province. Sampling was conducted from September 2012 to June 2013 at estuaries of Pakning, Bengkel and Jangkang rivers. We found seven species of puffer fish belongs to Tetraodontidae, they were grouped into 4 genera. Those fishes were Tetraodon nigroviridis, Tetraodon fluviatilis, Sphoeroideslunaris, Sphoeroides oblongatus, Chonerhinos amabilis, Chonerhinos sillus and Chelonodon patoca. The most abundant species is Tetraodon nigroviridis (25 individuals), while Chelonodon patoca one individual.